Pre- and post-competitive anxiety and match outcome in elite international junior tennis players - Fuentes-García, J. P.; Villafaina, S.; Martínez-Gallego, R.; Crespo, M. (International Journal of Sports Science & Coaching, 2023)
This study aimed to analyse the impact of match outcome (win or lose) in an elite international tennis competition on pre-competitive anxiety and self-confidence. A cohort of Under-16 elite boys (n = 18), with a mean age of 15.44 (0.616) years and an international competitive experience of 4.44 (1.89) years, which were representing six national teams participated in this cross-sectional study. The assessments took part in a qualifying stage of the International Tennis Federation (ITF) Junior Davis Cup competition. During the tournament, participants played the best of three set matches. The Competitive State Anxiety Inventory - 2R (CSAI-2R) and the State-Trait Anxiety Inventory (STAI-E) were employed to assess the pre-competitive anxiety before and after the tournament's match. Cognitive and somatic anxiety were slightly higher before than after the matches. No significant differences were found between the pre-and post-match measures. However, significant differences in cognitive anxiety, state anxiety and self-confidence were found when comparing pre-match and post-match values between winners and losers. In this regard, winners showed a significant reduction in state anxiety and cognitive anxiety after the match. According to our results, intervention programmes should incorporate tools that will assist players in their management of anxiety and self-confidence, specifically with those players who lost the match.